2023
DOI: 10.1039/d2fo04099a
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ca2+-calpain signaling is a new mechanism using Laminaria japonica polysaccharide to prevent macrophage foam cell formation and atherosclerosis

Abstract: The LJP61A suppressed macrophage foam cell formation and atherosclerotic progression by modulating Ca2+-calpain mediated autophagy inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Hoving et al found that mannose oligosaccharides could prevent worsening of atherosclerosis by reducing serum cholesterol levels and that these oligosaccharides may increase the butyric acid level in the cecum and promote excretion of bile acids by influencing the gut microbiome 78 . Li et al demonstrated that polysaccharides from Laminaria japonica suppressed atherosclerosis by increasing activity in the autophagy pathway 79 . Red algal polysaccharide has been investigated and may be a potential treatment for atherosclerosis 80 .…”
Section: Treatment Of Atherosclerosismentioning
confidence: 99%
“…Hoving et al found that mannose oligosaccharides could prevent worsening of atherosclerosis by reducing serum cholesterol levels and that these oligosaccharides may increase the butyric acid level in the cecum and promote excretion of bile acids by influencing the gut microbiome 78 . Li et al demonstrated that polysaccharides from Laminaria japonica suppressed atherosclerosis by increasing activity in the autophagy pathway 79 . Red algal polysaccharide has been investigated and may be a potential treatment for atherosclerosis 80 .…”
Section: Treatment Of Atherosclerosismentioning
confidence: 99%
“…LJP61A markedly reduces intracellular Ca 2+ to provoke macrophage autophagy, resulting in the suppression of lipid accumulation and AS. 135 …”
Section: Autophagy‐mediated Regulation In Macrophage Functionsmentioning
confidence: 99%
“…Frequently classified as a macrophage subtype, foam cells exhibit persistent residence within plaques, thereby contributing to the disease's progression 5 . Intracellular Ca 2+ overload in macrophages is identified as a powerful stimulant for oxidative stress and inflammatory responses, which in turn, aggravate atherosclerotic plaque formation and advancement 6 . Consequently, the assessment of intracellular Ca 2+ concentrations is fundamentally crucial to comprehend the pathophysiological mechanisms underpinning atherosclerosis development 7 …”
Section: Introductionmentioning
confidence: 99%